Habits of fluid and electrolytes intake in elite athletes (Journal of Health Sciences, 2015)
Introduction: Dehydration develops when the body fluid losses exceed fluid intake. It may occur during exercise, heat stress, restricted fluid intake, or any combination of these. Marginal dehydration (loss of > 2% body weight) can compromise aerobic exercise performance, particularly in hot weather conditions, and may disturb fluid and electrolyte balance. The aim of the study was to determine the quantity, type and dynamic of fluid intake during athletic performance in endurance sports (football and basketball) in two age categories: juniors (under the age of 18) and seniors (over the age of 18).Methods: Research included 100 athletes playing in Premier League in Bosnia-Herzegovina. We formed groups by sport type (football and basketball) and age (<18 and ≥18 years). Questionnaire with questions about the fluid intake habits was used for data collection. Results: There were 53 football players and 47 basketball players. All the participants were male. Average age of the participants was 19.3 ± 4.58. Habit of weighing before and after training was present in less than 44% of players among all the groups. Seniors were more frequently measuring their weight compared to junior players (p=0.01). Basketball players and players younger than 18 years were most frequently taking more than 2L of water per day. Most of the players, regardless of sport type or age group were not taking at least ½ L of isotonic fluid before the training. Signs of dehydration were more frequently observed in players under 18 years old, with most frequent sign being dry throat and sudden fatigue.Conclusion: Water and electrolytes intake before, during and after training of the athletes were inadequate regardless of type of sports and the age of athletes.